Family migration and the path to an occupation : the (early) experiences of skilled Taiwanese and Chinese 'wives' - Hsu, Chieh, 1985- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book sheds light on the invisible early post-arrival period of female family migrants, traditionally considered to be low-skilled or professionally quiescent. With attention to the experiences of Chinese and Taiwanese women married to German men, it examines the ways in which the private sphere - marked by intermarriage couple dynamics and native-foreigner relations - constitutes the main locus of women's socialization in the host country, as interactions with their intimate partners in the family realm shape both their self-conceptions, and their employment intentions. Based on interviews with migrant women and their spouses, the author outlines the subject positions that characterize female migrants' attitudes to external constructs and entering the labor market, showing that female family migrants frequently take on family migrant and wife roles that permeate intimate relationships and impede employment intentions, but also often strive to realign with their pre-departure independent selves and thus regain agency. A study of gender dynamics and labor market entry among newly arrived female migrants, this volume will appeal to scholars of sociology with interests in gender, migration and work"--
Part 1. Placing women in the migration context -- Professionals? Migrants? Wives? Who are these women? -- Women on and after the move -- Home country contexts v.s. host country realities -- Part 2. Understanding skilled "wives'" experiences -- An evolving self tied to roles: re-envisioning the immersion period -- An insider's approach -- Part 3. Navigating the new and bridging the gap -- marriage and dependency back home and in Germany -- Embracing dependency: passive autonomy -- Reclaiming independence: active autonomy.
OCLC-licensed vendor bibliographic record.
Keywords: Women immigrants -- Social conditions; Women immigrants -- Germany -- Social conditions; Chinese -- Foreign countries -- Social conditions; Taiwanese -- Foreign countries -- Social conditions; Chinese -- Germany -- Social conditions; Taiwanese -- Germany -- Social conditions; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General